Aerobic Exercise During Advance Stage of Uncontrolled Arterial Hypertension - Pagan, Luana U.; Gomes, Mariana J.; Damatto, Ricardo L.; Lima, Aline R. R.; Cezar, Marcelo D. M.; Damatto, Felipe C.; Reyes, David R. A.; Campos, Dijon H. S.; Caldonazo, Tulio M. M.; Polegato, Bertha F.; Fernandes, Denise C.; Laurindo, Francisco R.; et al. (Frontiers in Physiology, 2021)
Aim To evaluate the influence of physical training on myocardial function, oxidative stress, energy metabolism, and MAPKs and NF-κB signaling pathways in spontaneously hypertensive rats (SHR), at advanced stage of arterial hypertension, which precedes heart failure development. Methods We studied four experimental groups: normotensive Wistar rats (W, n = 27), trained W (W-EX, n = 31), SHR (n = 27), and exercised SHR (SHR-EX, n = 32). At 13 months old, the exercise groups underwent treadmill exercise 5 days a week for 4 months. In vitro myocardial function was analyzed in left ventricular (LV) papillary muscle preparations. Antioxidant enzyme activity and energy metabolism were assessed by spectrophotometry. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity was analyzed by lucigenin reduction and protein expression by Western blot. Statistical analyzes: ANOVA and Tukey or Kruskal–Wallis and Dunn tests. Results SHR-EX had a lower frequency of heart failure features than SHR. Myocardial function and antioxidant enzyme activity were better in SHR-EX than SHR. Lipid hydroperoxide concentration, and phosphorylated JNK and total IkB protein expression were higher in hypertensive than control groups. Malondialdehyde, NADPH oxidase activity, total JNK, phosphorylated p38, phosphorylated and total p65 NF-κB, and phosphorylated IkB did not differ between groups. Protein expression from total p38, and total and phosphorylated ERK were higher in SHR than W. Lactate dehydrogenase and phosphorylated ERK were lower and citrate synthase and β-hydroxyacyldehydrogenase were higher in SHR-EX than SHR. Conclusion Exercise improves physical capacity, myocardial function, and antioxidant enzyme activity; reduces the frequency of heart failure features and ERK phosphorylation; and normalizes energy metabolism in SHR.